STUDY OF ANALYTICAL WORK ON DATA PROCESSING IN INTELLIGENCE BODIES - Маміч, В.В.; Берназ, А.М.; Максименко, Ю.А.; Попов, С.А.; Шаршаткін, Д.Ю. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2022)
Abstract: Wide implementation of modern information technologies has become an urgent issue today, according to scientists, it is an absolute requirement of the time and has become an integral feature of the work of modern management bodies. In modern conditions in the field of information technologies, there have always been two mutually complementary directions of development: systems focused on operational data processing - data processing systems and systems focused on data analysis - decision support systems. At the current stage of informatization of analytical work, a new approach found its expression in the concepts of data banks (DB). The data bank is an information system that includes a set of special methods and tools to support the dynamic information model of the field of its application for the purpose of providing information to users. At the same time, the input information (prepared for input into the information model and that is the result of the operation of the information collection and registration subsystems in the ACS), as well as the output information (obtained as a result of the processing of the information included in the model and which is received at the input of the distribution subsystems and display of information in ACS) are not considered as part of the information model. The task of maintaining the information model in the required state is that the operations of preservation and modification of the information model are carried out in the BND in accordance with the emerging changes in the composition of the objects of the subject field, the connections between them and their state. The task of providing information requests of users has two aspects that must be taken into account when designing BnD. The first aspect is the definition of the boundaries of a specific subject area and the development of an appropriate information model. The second aspect is the development of a data bank focused on efficient service of user requests. To date, the introduction of a data bank and new information processing technologies will allow for a significant increase in speed and efficiency in the analytical work of intelligence and information units.

Актуальним питанням сьогодення стало широке впровадження сучасних інформаційних технологій, на думку вчених, воно є безумовною вимогою часу та стало невід’ємною відзнакою роботи сучасних органів управління. В сучасних умовах у галузі інформаційних технологій завжди існували два взаємодоповнюючих один одного напрямки розвитку: системи, орієнтовані на операційну обробку даних – системи обробки даних та системи,орієнтовані на аналіз даних – системи підтримки прийняття рішень. На сучасному етапі інформатизації аналітичної роботи новий підхід знайшов своє вираження в концепціях банків даних (БнД). Банк даних – це інформаційна система, що включає комплекс спеціальних методів і засобів для підтримки динамічної інформаційної моделі галузі свого застосування з метою інформаційного обслуговування користувачів. При цьому вхідна інформація (підготовлена до введення в інформаційну модель і така, що є результатом роботи підсистем збору і реєстрації інформації в АСУ), а також вихідна інформація (отримана в результаті обробки інформації, укладеної в моделі, і, що надходить на вхід підсистем розподілу і відображення інформації в АСУ) не розглядаються як частина інформаційної моделі. Задача підтримки інформаційної моделі в необхідному стані полягає в тому, щоб у БнД виконувалися операції збереження і модифікації інформаційної моделі відповідно до виникаючих змін в складі об’єктів предметної галузі, зв’язках між ними і їхнім станом. Задача забезпечення інформаційних запитів користувачів має два аспекти, які необхідно враховувати при проектуванні БнД. Перший аспект – це визначення меж конкретної предметної галузі і розробка відповідної інформаційної моделі. Другий аспект – розробка банку даних, орієнтованого на ефективне обслуговування запитів користувачів. На сьогоднішній день впровадження банку даних і нових технологій обробки інформації дозволить отримати значне підвищення швидкості та ефективності в аналітичної роботі розвідувально-інформаційних підрозділів.
ДОСЛІДЖЕННЯ АНАЛІТИЧНОЇ РОБОТИ З ОБРОБЛЕННЯ ДАННИХ В ОРГАНАХ РОЗВІДКИ
Keywords: структурована інформація; інформаційно-аналітична робота; алгоритм дій; інформаційні технології; інструмент боротьби; автоматизовані інформаційні системи; інформація як особливий вид ресурсу; structured information; information-analytical work; algorithm of actions; information technologies; tool of struggle; automated information systems; information as a special kind of resource